Strategy to prevent epitope masking in CAR.CD19+ B-cell leukemia blasts. Issue 6 (16th June 2021) - Quintarelli, Concetta; Guercio, Marika; Manni, Simona; Boffa, Iolanda; Sinibaldi, Matilde; Di Cecca, Stefano; Caruso, Simona; Abbaszadeh, Zeinab; Camera, Antonio; Cembrola, Biancamaria; Ciccone, Roselia; Orfao, Alberto; et al.
Abstract : Chimeric antigen receptor T-cells (CAR T-cells) for the treatment of relapsing/refractory B-cell precursor acute lymphoblastic leukemia have led to exciting clinical results. However, CAR T-cell approaches revealed a potential risk of CD19-/CAR+ leukemic relapse due to inadvertent transduction of leukemia cells. Background: Methods: We evaluated the impact of a high percentage of leukemia blast contamination in patient-derived starting material (SM) on CAR T-cell drug product (DP) manufacturing. In vitro as well as in vivo models were employed to identify characteristics of the construct associated with better profile of safety in case of inadvertent B-cell leukemia transduction during CAR T-cell manufacturing. Results: The presence of large amounts of CD19+ cells in SM did not affect the transduction level of DPs, as well as the CAR T-cell rate of expansion at the end of standard production of 14 days. DPs were deeply characterized by flow cytometry and molecular biology for Ig-rearrangements, showing that the level of B-cell contamination in DPs did not correlate with the percentage of CD19+ cells in SM, in the studied patient cohort. Moreover, we investigated whether CAR design may affect the control of CAR+ leukemia cells. We provided evidences that CAR.CD19 short linker (SL) prevents complete epitope masking in CD19+CAR+ leukemia cells and we demonstrated in vitro and in vivo that CD19 +CAR(SL)+leukemic cells are killed by CAR.CD19 T-cells. Conclusions: Taken together, these data suggest that a VL-VH SL may result in a safe CAR-T product, even when manufacturing starts from biological materials characterized by heavy contamination of leukemia blasts.